2015
DOI: 10.1002/ieam.1618
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and other trace elements in Ohio River fish collected near coal‐fired power plants: Interspecific patterns and consideration of consumption risks

Abstract: Many coal-fired electric generating facilities in the United States are discharging higher loads of Hg, Se, and other chemicals to receiving streams due to the installation of flue gas desulfurization (FGD) air pollution control units. There are regulatory concerns about the potential increased uptake of these bioaccumulative trace elements into food webs. We evaluated the concentrations of As, total Hg (THg), methylmercury (MeHg), and Se in Ohio River fish collected proximal to coal-fired power plants, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
4
6
1
Order By: Relevance
“…The muscle tissue trace element concentrations reported in the present study were generally similar to previous studies documenting Se and Hg fish tissue amounts for fish collected at reference locations in the Ohio River (Walters et al ; Reash et al ). In contrast, concentrations of THg in Ohio River hybrid striped bass recorded by Emery and Spaeth () were considerably higher relative to accumulations in the present study.…”
Section: Resultssupporting
confidence: 91%
“…The muscle tissue trace element concentrations reported in the present study were generally similar to previous studies documenting Se and Hg fish tissue amounts for fish collected at reference locations in the Ohio River (Walters et al ; Reash et al ). In contrast, concentrations of THg in Ohio River hybrid striped bass recorded by Emery and Spaeth () were considerably higher relative to accumulations in the present study.…”
Section: Resultssupporting
confidence: 91%
“…We found mean Se:THg molar ratios to be positive and above 1 in all species, concurrent with previous studies investigating Se:Hg molar ratios in freshwater fish ( Fig 4A) [24,25,94,95] though our ratios were much higher than other comparable species [24,25]. The higher values are presumably a result of the elevated Se concentrations found across the UCRB.…”
Section: Se:thg Molar Ratiossupporting
confidence: 91%
“…The low median percentage of THg as MeHg in samples from the current study (<2%) is similar to findings reported for samples collected at the same 4 Ohio River power plant intake locations and at various ambient locations (ORSANCO , ). The findings from this study support previous inferences that the methylation potential of the Ohio River is low (EPRI ; Reash et al ).…”
Section: Resultssupporting
confidence: 91%